Marketing Communication Strategy to Increase Tourist Visits to Tumpak Sewu Waterfall In Lumajang - Syarofa, Sherina; Priyo Sadono, Teguh; Sigit Pramono , Bambang (Green Publisher Indonesia, 2025)
The purpose of this research is to examine the Integrated Marketing Communication (IMC) strategy in increasing tourist visits to Tumpak Sewu Waterfall, Lumajang. Utilizing a descriptive qualitative model, data was gathered through in-depth interviews with local stakeholders, including the Tourism Agency, tour managers, and tourists. The results of the study show that all the main elements of IMC have been implemented, including advertising, personal selling, sales promotion, public relations, direct marketing, interactive marketing, and word of mouth. This strategy has proven effective in increasing the visibility and interest of both domestic and international tourists. Furthermore, the active participation of local communities, such as Pokdarwis and tour guides, also contributes to strengthening the tourist experience and enhancing the overall destination appeal. However, the research also identified several problems in the actualization of the IMC strategy, such as illegal collection practices, weak coordination in the management of Grojogan Sewu as a new destination, and the suboptimal utilization of the digital application